Modified MoSe2 piezoelectric catalyst as well as preparation method and application thereof
By introducing FeSe2 into MoSe2, a nanoflower-like structure is formed, which solves the problems of insufficient piezoelectric polarization and limited number of active sites of MoSe2, improves catalytic activity and piezoelectric properties, and realizes efficient application of upgrading and converting microplastics into CO.
Patent Information
- Application Number
- CN202510090961.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The practical application of MoSe2 is limited by its insufficient piezoelectric polarization, limited number of active sites, low free carrier concentration, and slow carrier separation and migration speed.
By replacing the Mo2+ part of the MoSe2 nanosheets with Fe2+, a randomly layered and superimposed structure is formed, showing a nanoflower-like structure, and catalytic activity and piezoelectric properties are improved.
The catalytic activity and piezoelectric properties of MoSe2 are improved, the edge active sites are increased, the piezoelectric catalytic activation efficiency of perdisulfate is improved, and the microplastic is upgraded to CO under ultrasonic conditions.
Smart Images

Figure CN119869564A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric catalysis technology, and in particular to a modified MoSe 2 Piezoelectric catalyst and its preparation method and application. Background Art
[0002] There are many kinds of piezoelectric catalysts currently in use, among which molybdenum diselenide (MoSe 2 As a typical transition metal chalcogenide, MoSe has piezoelectric properties due to its non-centrosymmetric crystal structure. In recent years, it has been widely used in many fields such as electrochemistry, adsorption, and catalysis. Compared with compounds with similar structures, MoSe 2 MoSe has a large piezoelectric response, good mechanical flexibility, and a large specific surface area, and is sensitive to small stresses, making it an ideal material for catalytic applications. 2 The practical applications of ions are often limited by their insufficient piezoelectric polarization, limited number of active sites, low free carrier concentration, and slow carrier separation and migration. Summary of the invention
[0003] Purpose of the invention: The first purpose of the present invention is to provide a modified MoSe with rich active sites, fast electron transport and high catalytic activity. 2 Piezoelectric catalyst; The second object of the present invention is to provide the modified MoSe 2 Preparation method of piezoelectric catalyst; The third object of the present invention is to provide the modified MoSe 2 Application of piezoelectric catalysts in the upcycling of microplastics into CO.
[0004] Technical solution: The modified MoSe described in the present invention 2 Piezoelectric catalyst, by MoSe 2 Mo in nanosheets 2+ Partly Fe 2+ Replacement, forming MoSe 2 Nanosheets and FeSe 2 The structure of randomly layered and stacked nanosheets presents a nanoflower-like structure.
[0005] MoSe 2 Nanosheets and FeSe 2 Nanosheets are ultra-thin nanosheets. 2 Introduction of FeSe into nanosheets 2 Improved MoSe 2 The catalytic activity of the nanosheets, and the nanoflower-like structure is conducive to inducing the occurrence of piezoelectric polarization, and can also expose more edge active sites, thereby improving the piezoelectric catalytic activation efficiency of peroxydisulfate.
[0006] Preferably, the MoSe 2 Nanosheets and FeSe 2 The molar ratio of nanosheets is 15:1 to 5. 2 As the amount of FeSe increases, the number of heterojunctions formed between the two materials increases, and the piezoelectric performance improves; 2 Too much introduction may affect MoSe 2 The piezoelectric properties of the material.
[0007] Modified MoSe according to the present invention 2 The preparation method of the piezoelectric catalyst comprises the following steps: 2 The powder is evenly dispersed in water, and then iron salt and hydrazine hydrate are added and mixed thoroughly for hydrothermal reaction. 2 Mo in 2+ Partly Fe 2+ Replace to obtain the modified MoSe 2 Piezoelectric catalyst.
[0008] During the hydrothermal reaction, MoSe 2 As selenium source, iron salt as iron source, hydrazine hydrate as reducing agent. Hydrazine hydrate can reduce Fe 3+ Reduction to Fe 2+ , MoSe 2 Mo in molecules 2+ Partially replaced by Fe 2+ , thereby generating part of FeSe 2 , FeSe 2 In situ growth on MoSe 2 On the surface, it presents a nanoflower-like structure.
[0009] Preferably, the hydrothermal reaction temperature is 180-220°C.
[0010] Preferably, the hydrothermal reaction time is 22 to 26 hours.
[0011] Preferably, the iron salt is ferric chloride hexahydrate.
[0012] Preferably, the ferric chloride hexahydrate and MoSe 2 The mass ratio is 3 to 12:40.
[0013] The MoSe 2The powder was prepared by dissolving 0.608 g of sodium borohydride in 150 mL of deionized water, then mixing 0.632 g of selenium powder and 0.968 g of sodium molybdate with the mixture and stirring for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction. After natural cooling, the mixture was washed with deionized water and anhydrous ethanol three times respectively, and dried under vacuum overnight to obtain MoSe 2 powder.
[0014] Preferably, the hydrothermal temperature is 200-220° C., and the hydrothermal time is 18-22 hours.
[0015] Preferably, the drying temperature is 50-65° C., and the drying time is 12-18 hours.
[0016] Modified MoSe according to the present invention 2 Application of piezoelectric catalysts in the upcycling of microplastics into CO.
[0017] Preferably, the application method is: uniformly dispersing the prepared catalyst in an aqueous solution containing microplastics, adding peroxydisulfate to initiate a piezoelectric catalytic reaction to produce CO, and the piezoelectric catalytic reaction is carried out in an air-closed system using an ultrasonic cleaning machine.
[0018] Invention mechanism: The present invention adopts MoSe 2 With FeSe 2 The composite is used as a piezoelectric catalyst. The introduction of Fe increases the concentration of free carriers in the material and accelerates the separation and migration of carriers. 2 / FeSe 2 The content of iron in the composite material, and finally determine the MoSe with the optimal iron content 2 / FeSe 2 Piezoelectric catalyst.
[0019] MoSe 2 With FeSe 2 The nanoflower-shaped structure is not only conducive to inducing the occurrence of piezoelectric polarization, but also can expose more edge active sites, thereby improving the piezoelectric catalytic activation efficiency of peroxydisulfate. The catalyst can upgrade microplastics into CO under ultrasonic conditions, avoiding the production of greenhouse gases, and does not require light or heating, thus reducing the difficulty of practical application.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) by 2 FeSe 2 , which increases the concentration of free carriers in the material, accelerates the separation and migration of carriers, and improves the MoSe 2The catalytic activity of the catalyst is good, and the nanoflower-shaped structure is not only conducive to the induction of piezoelectric polarization, but also can expose more edge active sites, thereby improving the piezoelectric catalytic activation efficiency of peroxydisulfate; (2) The catalyst is prepared by a hydrothermal method, and the raw materials are simple and easy to obtain, the cost is low, the preparation process is simple, the preparation conditions are mild, it is energy-saving and environmentally friendly, and it is easy to achieve large-scale production; (3) The catalyst is used to upgrade microplastics into CO, avoiding the production of greenhouse gases, and does not require light, heating and other conditions, reducing the difficulty of practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the XRD diagram of the catalyst in Examples 1 to 3 and Comparative Example 1;
[0022] Figure 2 is the Raman characterization graph of the catalysts in Examples 1 to 3 and Comparative Example 1;
[0023] Figure 3 is a transmission electron microscope image of the catalyst in Comparative Example 1;
[0024] Figure 4 is a transmission electron microscope image of the catalyst in Example 2;
[0025] Figure 5 It is a performance diagram of the catalyst in Examples 1 to 3 and Comparative Example 1 converting 10 mg of polylactic acid into CO;
[0026] Figure 6 is a graph of CO production of the catalyst in Example 2 at different polylactic acid dosages;
[0027] Figure 7 This is a stability performance diagram of the catalyst in Example 2 converting 20 mg of polylactic acid into CO. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with embodiments.
[0029] Example 1 (MoSe 2 / FeSe 2 -15)
[0030] Modified MoSe of the present invention 2 Piezoelectric catalysts, including MoSe 2 Nanosheets and FeSe 2 The molar ratio of the nanosheets is 14.17:1; the preparation method comprises the following steps:
[0031] (1) MoSe 2 Powder preparation
[0032] 0.608 g of sodium borohydride was dissolved in 150 mL of deionized water, and then 0.632 g of selenium powder and 0.968 g of sodium molybdate were fully mixed and stirred for 30 min. The resulting mixture was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 210 ° C for 20 h. After natural cooling, it was washed with deionized water and anhydrous ethanol three times respectively, and dried under vacuum overnight to obtain MoSe 2 powder.
[0033] (2) MoSe 2 / FeSe 2 Preparation of -15
[0034] 200mg MoSe 2 The powder was evenly dispersed in 30 mL of deionized water, and then 15 mg of ferric chloride hexahydrate and 4 mL of hydrazine hydrate were fully mixed with it. The resulting mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 200 °C for 24 h. After cooling to room temperature, it was centrifuged, washed, dried, and ground to obtain MoSe 2 / FeSe 2 Piezoelectric catalyst, named MoSe 2 / FeSe 2 -15.
[0035] Example 2 (MoSe 2 / FeSe 2 -40)
[0036] Modified MoSe of the present invention 2 Piezoelectric catalysts, including MoSe 2 Nanosheets and FeSe 2 The molar ratio of the nanosheets is 5.31:1; the preparation method comprises the following steps:
[0037] (1) MoSe 2 The preparation of powder is the same as in Example 1.
[0038] (2) MoSe 2 / FeSe 2 Preparation of -40
[0039] 200mg MoSe 2 The powder was evenly dispersed in 30 mL of deionized water, and then 40 mg of ferric chloride hexahydrate and 4 mL of hydrazine hydrate were fully mixed with it. The resulting mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 200 °C for 24 h. After cooling to room temperature, it was centrifuged, washed, dried, and ground to obtain MoSe 2 / FeSe 2 Piezoelectric catalyst, named MoSe 2 / FeSe 2 -40.
[0040] Example 3 (MoSe 2 / FeSe 2 -60)
[0041] Modified MoSe of the present invention 2 Piezoelectric catalysts, including MoSe 2 Nanosheets and FeSe 2 The molar ratio of the nanosheets is 3.54:1; the preparation method comprises the following steps:
[0042] (1) MoSe 2 The preparation of powder is the same as in Example 1.
[0043] (2) MoSe 2 / FeSe 2 Preparation of -60
[0044] 200mg MoSe 2 The powder was evenly dispersed in 30 mL of deionized water, and then 60 mg of ferric chloride hexahydrate and 4 mL of hydrazine hydrate were fully mixed with it. The resulting mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 200 °C for 24 h. After cooling to room temperature, it was centrifuged, washed, dried, and ground to obtain MoSe 2 / FeSe 2 Piezoelectric catalyst, named MoSe 2 / FeSe 2 -60.
[0045] Comparative Example 1 (MoSe 2 )
[0046] Only step (1) of Example 1 is performed to obtain MoSe 2 Piezoelectric catalyst.
[0047] Structural characterization
[0048] The different catalysts prepared in Examples 1 to 3 and Comparative Example 1 were characterized by X-ray diffraction (XRD). Figure 1 shown.
[0049] Depend on Figure 1 It can be seen that Examples 1 to 3 and Comparative Example 1 all have 1T phase MoSe 2 , and 2H phase MoSe 2 Compared with 1T phase MoSe 2 Due to its relatively high electronic conductivity, it exhibits better catalytic activity. Among them, the XRD spectra of Examples 1 to 3 show obvious 2The relevant characteristic peaks are consistent with the standard card of orthorhombic iron ore (JCPDSNo:74-0247).
[0050] The different catalysts prepared in Examples 1 to 3 and Comparative Example 1 were characterized by Raman spectroscopy. Figure 2 shown.
[0051] Depend on Figure 2 It can be seen that Examples 1 to 3 and Comparative Example 1 have a -1 A small but weak out-of-plane Mo-Se mode of the 2H phase is observed at 1g ) peak. In addition, J1, J2, E 1g 、E 2g 1 The vibration modes of J3 and J4 are 114.1cm -1 、149.2cm -1 、197.9cm -1 、282.4cm -1 and 337.0cm -1 , which is the main signal to distinguish the 1T phase from the 2H phase. Several catalysts all showed similar characteristic peaks, and the 1T phase signal was significantly stronger than the 2H phase signal, indicating that the 1T phase mainly existed in the sample. Therefore, the above results show that Examples 1 to 3 and Comparative Example 1 were successfully prepared.
[0052] The different catalysts prepared in Example 2 and Comparative Example 1 were characterized by transmission electron microscopy (TEM). Figures 3-4 shown.
[0053] from Figure 3 and Figure 4 It can be seen that the prepared MoSe 2 and MoSe 2 / FeSe 2 -40 are composed of randomly layered ultra-thin nanosheets to form a nanoflower-like structure, which helps to increase the specific surface area of the catalyst, provide more edge active sites, and thus improve the catalytic efficiency.
[0054] Performance Testing
[0055] 1. Catalyst-catalyzed polylactic acid (PLA) conversion to CO production test
[0056] MoSe of the present invention 2 / FeSe 2 The application of piezoelectric catalysts in the upgrading and conversion of microplastics is specifically applied to the conversion of polylactic acid (PLA) into CO. The application method includes the following steps:
[0057] (1) 30 mg of the catalyst was placed in a reactor containing 50 mL of an aqueous solution containing a certain amount (5 mg, 10 mg, or 20 mg) of PLA;
[0058] (2) The sealed reactor was flushed three times with an oil pump while being kept under an argon atmosphere to ensure complete removal of air;
[0059] (3) The reactor was pressurized to 1 bar with argon, and 90 mg of peroxydisulfate was added to the system to initiate the piezoelectric catalytic reaction;
[0060] (4) The piezoelectric catalytic reaction was carried out in a closed air system using an ultrasonic cleaner (120 W, 40 kHz). The reaction system was maintained at 25 °C under the control of a low-temperature circulation pump, and the gas mixture was collected at 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4 h.
[0061] (5) The CO concentration was detected by a hydrogen flame ionization detector (FID).
[0062] 10 mg PLA was added to the reaction system. The CO production of Examples 1 to 3 and Comparative Example 1 was as follows: Figure 5 shown.
[0063] Depend on Figure 5 It can be seen that the CO production of the catalysts prepared in Examples 1 to 3 and Comparative Example 1 within 4 hours is 41.07 μmol g -1 、65.49μmol g -1 , 48.55 μmol g -1 , 2.88 μmol g -1 The catalyst prepared in Example 2 has the highest CO production. Compared with Example 2, the conversion rate of activated peroxydisulfate to PLA in Comparative Example 1 is significantly lower, which may be due to the fact that MoSe 2 and FeSe 2 The combination of can not only provide multiple pathways to activate peroxydisulfate, but also promote Fe 3+ / Fe 2+ Therefore, MoSe 2 / FeSe 2 -40 can be used as an efficient piezoelectric catalyst for the upgrading and conversion of microplastics.
[0064] 2. Test on the production of polylactic acid (PLA) converted into CO by adding different amounts of catalyst
[0065] Example 2 CO production at different PLA dosages Figure 6 shown.
[0066] Depend on Figure 6 It can be seen that with the increase of PLA dosage, MoSe2 / FeSe 2 -40 to PLA conversion rate continued to increase, 20mgPLA dosage of CO production was the highest, which may be due to the reaction system to provide more carbon source.
[0067] 3. Catalyst cycle stability test
[0068] 20 mg PLA was added to the reaction system, and the catalyst prepared in Example 2 was subjected to a cyclic stability test. The test method was as follows: In the cyclic stability test, after each CO determination experiment was completed, the catalyst was collected, fully washed and dried, and then the next catalytic experiment was carried out.
[0069] The results are as follows Figure 7 As shown. Figure 7 It can be seen that after the catalyst was run for four consecutive times, the CO production increased from 87.65 μmol g -1 Slightly decreased to 83.16 μmol g -1 The reason for this decline is mainly due to the fact that the intermediates in the PLA reaction process cover the active sites of the catalyst. In general, the catalyst still shows good stability and excellent reusability.
Claims
1. A modified MoSe2 piezoelectric catalyst, characterized in that: By 2+ Partly Fe 2+ Replacement forms a structure in which MoSe2 nanosheets and FeSe2 nanosheets are randomly layered and stacked, presenting a nanoflower shape.
2. The modified MoSe2 piezoelectric catalyst according to claim 1, characterized in that The molar ratio of the MoSe2 nanosheets to the FeSe2 nanosheets is 15:1-5.
3. The modified MoSe2 piezoelectric catalyst according to claim 1, characterized in that The molar ratio of the MoSe2 nanosheets to the FeSe2 nanosheets is 15:2-3.
4. A method for preparing the modified MoSe2 piezoelectric catalyst according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly dispersing MoSe2 powder in water, then adding iron salt and hydrazine hydrate, mixing them thoroughly and performing a hydrothermal reaction, and the Mo in MoSe2 2+ Partly Fe 2+ Replacement to obtain the modified MoSe2 piezoelectric catalyst.
5. The method for preparing the modified MoSe2 piezoelectric catalyst according to claim 4, characterized in that: The hydrothermal reaction temperature is 180-220°C.
6. The method for preparing the modified MoSe2 piezoelectric catalyst according to claim 5, characterized in that: The hydrothermal reaction time is 22 to 26 hours.
7. The method for preparing the modified MoSe2 piezoelectric catalyst according to claim 4, characterized in that: The iron salt is ferric chloride hexahydrate.
8. The method for preparing the modified MoSe2 piezoelectric catalyst according to claim 7, characterized in that: The mass ratio of the ferric chloride hexahydrate to MoSe2 is 3-12:
40.
9. Use of the modified MoSe2 piezoelectric catalyst according to any one of claims 1 to 3 in upgrading microplastics into CO.
10. The use according to claim 9, characterized in that: The application method is: uniformly dispersing the prepared catalyst in an aqueous solution containing microplastics, adding peroxydisulfate to initiate a piezoelectric catalytic reaction to produce CO, and the piezoelectric catalytic reaction is carried out in an air-closed system using an ultrasonic cleaning machine.
Citation Information
Patent Citations
Z-scheme heterostructure photocatalyst,preparation method, and application thereof
CA3132174A1
Preparation method of iron-based piezoelectric catalytic material and application of iron-based piezoelectric catalytic material in water treatment
CN111495392A
Tungsten diselenide or molybdenum diselenide / gold nanoparticle composite material and preparation method thereof
CN113952966A
High-performance one-dimensional FeSe2-two-dimensional MoSe2 compound as well as preparation method and application thereof
CN114272940A
THREE-DIMENSIONAL POROUS NiSe2 FOAM-BASED HYBRID CATALYSTS FOR ULTRA-EFFICIENT HYDROGEN EVOLUTION REACTION IN WATER SPLITTING
US20190218674A1